2022
DOI: 10.3390/molecules27175678
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical and Pharmacological Research Progress on a Kind of Chinese Herbal Medicine, Fructus Malvae

Abstract: Since the outbreak of the COVID-19 pandemic, traditional Chinese medicine has played an important role in the treatment process. Furthermore, the discovery of artemisinin in Artemisia annua has reduced the incidence of malaria all over the world. Therefore, it is becoming urgent and important to establish a novel method of conducting systematic research on Chinese herbal medicine, improving the medicinal utilization value of traditional Chinese medicine and bringing great benefits to human health all over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 62%
“…In this study, the adverse events in both the control group and the observation group were low and the difference was not statistically signi cant, which suggests that combining glucocorticoids with RAS blockers plus MHCD did not increase the risk of adverse events while improving the e cacy. In addition, MHCD can bene t qi, activate blood, detoxi e and resolve blood stasis, and modern pharmacology con rms that Astragalus, Radix Paeoniae Alba, Radix Paeoniae Lacti orae, Fenghuang, Radix et Rhizoma Alba, and Andrographis paniculatae all have the effects of regulating mucosal immunity and attenuating renal brosis [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although ulcerative colitis is a complex systemic disease, chronic inflammation is still one of the main factors, and cohosh has an obvious effect of inhibiting inflammatory factors, which is consistent with the "elimination" of all drugs recorded in ancient books of traditional Chinese medicine. Chen Liyi et al also found that cohosh could inhibit the release of inflammatory mediators, regulating the expression of inflammation-related mediators, and regulate neutrophils [14] . It can be seen that cohosh is indeed the dominant drug in the treatment of inflammation.…”
Section: Modern Study Of Cohoshmentioning
confidence: 98%
“…The study findings of Liu Yinze et al [13] indicated that when using cohosh to treat ulcerative colitis caused by inflammation, adding cohosh to the treatment with basic drugs can effectively improve the treatment effect and delay the occurrence and development of the disease to a certain extent. Its mechanism of action may be due to the inflammatory factor interferon-γand interleukin (Interleukin, IL) -6 secreted components [14] . Although ulcerative colitis is a complex systemic disease, chronic inflammation is still one of the main factors, and cohosh has an obvious effect of inhibiting inflammatory factors, which is consistent with the "elimination" of all drugs recorded in ancient books of traditional Chinese medicine.…”
Section: Modern Study Of Cohoshmentioning
confidence: 99%